Proposing new teaching and welfare practice to assist Autistic Spectrum Disorder (ASD) pupils transitioning from mainstream secondary education, through a systematic review of Savant Syndrome literature. - Gilbert, David (2017)
This research examines how examples of successful techniques used to teach savant syndrome pupils could potentially be used in assisting mainstream students on the autistic spectrum to learn in, and transition from, a secondary school environment, into further education and beyond. Such an examination is undertaken through the means of a systematic literature review. A process of elimination, selection and examination of a wide range of literature relating to savant syndrome education was undertaken. From this key thematic aspects of practice relating to the physical environments of learning, pupil socialization and communication, cognition and neurological development, pupil talents, emotional well-being, creativity development and curriculum and teaching processes, were used to formulate ideas for new teaching and welfare practice in mainstream schools that could assist ASD students in these contexts to transition on from them. These recommendations were then tested with a group of ‘critical friends’, fellow education professionals from a variety of contexts, to see if they could assist in refining and developing them further. From these discussions a final model for partnership between mainstream secondary schools and FE Colleges to support students on the Autistic Spectrum in transitioning between such institutions was finalised, giving recommendations for intra institutional, inter institutional and individualised practice that could be adapted and used in actuality by schools and colleges in future research.